2023
DOI: 10.1155/2023/4628625
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Exploration of Sand Flies in Human Communities Affected by Cutaneous and Visceral Leishmaniasis in El Hajeb Province, Morocco

Abstract: Sand flies are the exclusive vectors of leishmaniasis. This group of parasitic diseases is a serious public health problem in Morocco. The aim of this study was to investigate the sand fly fauna, mainly the species composition, biodiversity, and seasonal activity of sand flies in El Hajeb in central Morocco. A total of six stations (Aït Naaman, Aït Rbaa, Aït Brahim, Ain Taoujdate, Sidi Mbarek, and Aït Oufella) were studied, five of which had recently recorded cases of leishmaniasis. Sand fly bimonthly captures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Cutaneous leishmaniasis (CL) is a group of neglected tropical diseases of parasitic origin caused by protozoa of the Leishmania genus transmitted by the bite of infected female sandflies, insects of the genus Lutzomyia in the New World; and the genus Phlebotomus in the Old World. [1][2][3][4][5] These insects are a health problem in many countries around the world. 6,7,8 They are skin lesions that produce loss of self-esteem, anxiety, and social stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous leishmaniasis (CL) is a group of neglected tropical diseases of parasitic origin caused by protozoa of the Leishmania genus transmitted by the bite of infected female sandflies, insects of the genus Lutzomyia in the New World; and the genus Phlebotomus in the Old World. [1][2][3][4][5] These insects are a health problem in many countries around the world. 6,7,8 They are skin lesions that produce loss of self-esteem, anxiety, and social stigma.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Studies have also shown the therapeutic effects of thyme on skin ulcers caused by leishmaniasis in rats, and also as a traditional herbal treatment to combat the insect vectors that transmit leishmaniasis, providing antimicrobial, antioxidant, and insecticidal activities. [21][22][23][24][25][26] Since the 1990s, several studies have been carried out on the effects of essential oils on the zootechnical performance of poultry especially…”
mentioning
confidence: 99%